Deciphering the signaling networks underlying simvastatin-induced apoptosis in human cancer cells: evidence for non-canonical activation of RhoA and Rac1 GTPases - Zhu, Y.; Casey, P.; Kumar, Alan Prem; Pervaiz, S. (Nature Publishing Group, 2013)
Although statins are known to inhibit proliferation and induce death in a number of cancer cell types, the mechanisms through which downregulation of the mevalonate (MVA) pathway activates death signaling remain poorly understood. Here we set out to unravel the signaling networks downstream of the MVA pathway that mediate the death-inducing activity of simvastatin. Consistent with previous reports, exogenously added geranylgeranyl pyrophosphate, but not Farnesyl pyrophosphate, prevented simvastatin’s growth-inhibitory effect, thereby suggesting the involvement of geranylgeranylated proteins such as Rho GTPases in the anticancer activity of simvastatin. Indeed, simvastatin treatment led to increased levels of unprenylated Ras homolog gene family, member A (RhoA), Ras-related C3 botulinum toxin substrate 1 (Rac1) and cell division cycle 42 (Cdc42). Intriguingly, instead of inhibiting the functions of Rho GTPases as was expected with loss of prenylation, simvastatin caused a paradoxical increase in the GTP-bound forms of RhoA, Rac1 and Cdc42. Furthermore, simvastatin disrupted the binding of Rho GTPases with the cytosolic inhibitor Rho GDIa, which provides a potential mechanism for GTP loading of the cytosolic Rho GTPases. We also show that the unprenylated RhoA- and Rac1-GTP retained at least part of their functional activities, as evidenced by the increase in intracellular superoxide production and JNK activation in response to simvastatin. Notably, blocking superoxide production attenuated JNK activation as well as cell death induced by simvastatin.Finally, we provide evidence for the involvement of the B-cell lymphoma protein 2 family, Bcl-2-interacting mediator (Bim), in a JNK-dependent manner, in the apoptosis-inducing activity of simvastatin. Taken together, our data highlight the critical role of non-canonical regulation of Rho GTPases and involvement of downstream superoxide-mediated activation of JNK pathway in the anticancer activity of simvastatin, which would have potential clinical implications.